A Comparison of Monochromatic and Mixed LED Light Color on Performance, Bone Mineral Density, Meat and Blood Properties, and Immunity of Broiler Chicks - Md. Rakibul Hassan; Shabiha Sultana; Ho S. Choe; Kyeong S. Ryu (The Journal of Poultry Science, 2014)
An experiment was conducted to investigate the effect of monochromatic and mixed light color on performance, bone, meat quality, blood properties and immunity of broiler chicks. In experiment 1, 1,200 Ross×Ross 1-day old chicks were equally allotted to the following 8 light treatments with 3 replications: red (R), yellow (Y) green (G), blue (B), mixed R×Y, Y×G, and G×B light colors. Fluorescent white light was the control. Experiment 2 considered similar treatments (6 treatments with 4 replications) except R and R×Y were not tested. Light (24 L: 0 D) and intensity (0.1 watts/m2) was maintained at the bird’s head level. Weight gain during weeks 2-3 increased in the G and G×B groups (P<0.05). Weight gain was higher (P<0.05) in the B and G×B treatments at week’s 4-5. Similar weight gains were noted in experiment 2. Monochromatic B and the G×B mixed lighting groups showed increased meat pH, decreased shear force, and L* in both experiments. Birds reared under B light had reduced (P<0.05) blood glucose in both experiments and reduced HDL and LDL levels in experiment 1. Circulating levels of IgG and IgA were increased with exposure to the monochromatic Y and G treatments at 21 days and to B light at 35 days of age (P<0.05). In conclusion, the mixed G×B lighting treatment enhanced growth performance and showed similar bone and blood properties and immunity of broiler chicks compared to those of monochromatic G or B light.